TRANSFORMASI DIGITAL DAN MODEL KERJA HYBRID: IMPLIKASI UNTUK MANAJEMEN SUMBER DAYA MANUSIA - Hidayat, Muhammad Irfan; Yaksibun, Yaksibun; Muhammad Arifin; Yudhinanto CN (Nusantara Hasana Journal, 2025)
Digital transformation and the implementation of hybrid work models have brought significant changes to Human Resource Management (HRM) practices. This article aims to analyze the impact of digital transformation and hybrid work on HRM functions, particularly in recruitment, employee development, performance management, and the strategic role of HRM within organizations. This study employs a literature review method by examining national and international academic journals published within the last five years (2021–2025). The findings indicate that digital transformation and hybrid work can enhance operational efficiency, work flexibility, employee satisfaction, and organizational performance when supported by adaptive and data-driven HRM policies. Nevertheless, these practices also present challenges related to employee engagement, organizational culture, and performance evaluation systems. Therefore, HRM is required to assume a more strategic role in managing change to ensure sustainable organizational success.